2019
DOI: 10.1177/0954410019867575
|View full text |Cite
|
Sign up to set email alerts
|

A finite-time H-infinite adaptive fault-tolerant controller considering time delay for flutter suppression of airfoil flutter

Abstract: To suppress airfoil flutter, a lot of control methods have been proposed, such as classical control methods and optimal control methods. However, these methods did not consider the influence of actuator faults and control delay. This paper proposes a new finite-time H∞ adaptive fault-tolerant flutter controller by radial basis function neural network technology and adaptive fault-tolerant control method, taking into account actuator faults, control delay, modeling uncertainties, and external disturbances. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It can be found that, compared with the uncontrolled aeroelastic system, a small feedback time‐delay can enhance the flutter boundary, while a large value of the feedback time‐delay will reduce the aeroelastic stability of the airfoil. Gao et al 153 designed a finite‐time adaptive fault‐tolerant dither controller based on neural network technology and adaptive fault‐tolerant control method to suppress the flutter of a 2D airfoil. The effectiveness and robustness of the control method were proved through numerical simulations.…”
Section: Research Contents and Methods Of Flutter Controlmentioning
confidence: 99%
“…It can be found that, compared with the uncontrolled aeroelastic system, a small feedback time‐delay can enhance the flutter boundary, while a large value of the feedback time‐delay will reduce the aeroelastic stability of the airfoil. Gao et al 153 designed a finite‐time adaptive fault‐tolerant dither controller based on neural network technology and adaptive fault‐tolerant control method to suppress the flutter of a 2D airfoil. The effectiveness and robustness of the control method were proved through numerical simulations.…”
Section: Research Contents and Methods Of Flutter Controlmentioning
confidence: 99%
“…The ASP property implies that exists a constant output feedback gain that makes the plant strictly passive (Rusnak and Barkana, 2009) (Barkana, 2016) and that the system transfer function fulfill the Almost Strictly Positive Realness ASPR condition. For a SISO transfer function the ASPR condition implies that its relative degree is 1, the leading coefficient of its numerator is positive and all its zeros are in the left half complex plane (Matsuki et al, 2018) (Iwai et al, 2006). However, almost all real systems do not comply with the ASPR condition; thus, to apply the SAC control algorithm, an augmented plant is defined by adding a Parallel Feed-forward Compensator PFC (Barkana, 2007).…”
Section: Simple Adaptive Controller-sacmentioning
confidence: 99%
“…Jia et al (2019, 2021) proposed a data-driven optimal controller which eliminates the effects of non-modeled dynamics and uncertainties. Ming-Zhou et al (2020) proposed a finite-time H adaptive fault-tolerant control that takes into account control delay, uncertainties, and disturbances.…”
Section: Introductionmentioning
confidence: 99%